Social movements in contemporary Peru: a theoretical and methodological approach - Moscoso Carbonel, Emilia Hortencia (2024)
At present, in Peru, social networks based on the new Information and Communication Technologies (ICT) have become important elements in the configuration and dynamics of collective actions. In this panorama, the collective actors have modified their forms of organization, communication and convocation, creating alternative public spaces that facilitate the achievement of their common objectives. However, this new communication ecosystem can be the scene of misinformation, surveillance and social polarization. For these reasons, the main objective of this research is to provide a theoretical and methodological approach that facilitates the understanding of recent collective actions that use technologies to enrich their mobilizing potential. To do this, the social and political dynamics in the transit of the media to social networks are analyzed, some key theories about collective actions are examined, a panoramic perspective of the movements in contemporary Peru is offered and, finally, some methodological routes are proposed.